Hydroclimatic and Geological Conditions of the Variability of Fluvial Transport Rate in the Upper Part of the Wieprz River Catchment - Świeca, Andrzej; Kociuba, Waldemar; Brzezińska-Wójcik, Teresa (Quaestiones Geographicae, 2015)
The article summarises the results of observations conducted in the periods 1989-1992, 1998-2000, and 2001- 2003 in the catchment of the Roztocze section of the Wieprz River with an area of 404 km2. The presented results of the study on fluvial transport document the response of an upland river to variable hydro-climatic conditions. Fluvial transport rate in periods extreme in hydrological terms was compared. In the conditions of low water stages (1989- 1992) and mean annual discharges lower than the mean multiannual by 19%, the Wieprz River discharged an average of 13300 tonnes of solutions and 485 tonnes of suspensions annually. The unitary indices amounted to 32.7 and 1.2 t/ km2/year, respectively. In the years 1998-2000, in the conditions of high water stages and mean annual discharges higher than the multiannual by 41%, the Wieprz River discharged approximately 22,800 tonnes of solutions and 981 tonnes of suspensions annually. The unitary indices increased proportionately to 56.2 t/km2/year and 2.4 t/km2/year, respectively. In the years 2001-2003, in the conditions of variable water stages and discharges higher than the multiannual by 12%, the Wieprz River discharged an average of approximately 17,500 tonnes of solutions and 441 tonnes of suspensions annually. The unitary indices reached the values of 43.3 t/km2/year and 1.1 t/km2/year, respectively.